INDEKS GLIKEMIK COOKIES SORGUM (SORGHUM BICOLOR) DENGAN PENAMBAHAN TEPUNG KACANG MERAH (PHASEOLUS VULGARIS) PRATANAK - Tri Kusuma Agung Puruhita (JURNAL RISET GIZI, 2020)
Background: The prevalence of diabetes is increasing, one of the pillars of intervention is the provision of high-fiber or complex carbohydrates food. Sorghum as local food has the potential to manufacture as cookies diabetes because it contains fiber and low glycemic index. Foods with a low glycemic index help to prevent against high blood glucose fluctuation. Levels of resistant starch can be improved with the addition of parboiled red beans fluor. Parboiled process aims to improve the digestibility and resistant starch level of red beans. Objective: Determine parboiled red beans fluor % addition which still preferred by consumer panelists, and then determine the glycemic index of cookies sorghum with the addition of selected parboiled red beans fluor. Methods: Experimental study, the first stage was organoleptic test with randomized block design. 6 treatments of parboiled red bean flour and three replications. The addition consists of 0, 10, 20, 30, 40, and 50%. The second stage was the determination of the glycemic index. The subject had to fasting for 10 hours, consumed white bread, and then measured the glycemic response at 0, 30, 60, 90, 120 minute. Four days later the same step repeated with cookies sorghum as food had to consumed. Glycemic index values determined by comparing the inceremental area under curve of cookies sorghum with the incremental area under curve of white bread. Results: The addition of parboiled red bean flour preference is 30%. Cookies sorgum glycemic index was 48.5Conclusion: Cookies sorghum can be used as a snack food for healthy people because it has a low glycemic index